2007
DOI: 10.4145/jahs.37.187
|View full text |Cite
|
Sign up to set email alerts
|

Literature review of stemflow generation and chemical characteristics in Japanese forests

Abstract: Stemflow has a significant influence on hydrological and ecological processes within forests. However, research on stemflow is scant as stemflow comprises a very small volume compared to throughfall. In Japan, forest cover mainly distributed in mountainous areas occupies nearly 70% of the total land area and ranges from subalpine to subtropical zones. Many hydrological and agricultural studies have been conducted but a comprehensive literature review that summarizes the generation and chemical characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
(29 reference statements)
1
6
0
Order By: Relevance
“…Mean throughfall inputs are reported to range from 27 to 96%, while canopy interception loss is reported to range from 9.7 to 19.5% in various deciduous forests (Price and Carlyle-Moses 2003). In Japan, the range of throughfall has been reported at 64-97% (Ikawa 2007). Throughfall above bamboo (88.4%) and canopy interception (11.6%) measured at this study site were within the ranges reported from other forests.…”
Section: Water Budgets and Dissolved Organic Carbon Flux During The Gsupporting
confidence: 63%
“…Mean throughfall inputs are reported to range from 27 to 96%, while canopy interception loss is reported to range from 9.7 to 19.5% in various deciduous forests (Price and Carlyle-Moses 2003). In Japan, the range of throughfall has been reported at 64-97% (Ikawa 2007). Throughfall above bamboo (88.4%) and canopy interception (11.6%) measured at this study site were within the ranges reported from other forests.…”
Section: Water Budgets and Dissolved Organic Carbon Flux During The Gsupporting
confidence: 63%
“…Ikawa (2007) reported that percents of throughfall and stemflow to gross rainfall range between 64 and 97% and between 1 and 20%, respectively, in Japanese forests. Therefore, the values of this study are within the reported values.…”
Section: Discussionmentioning
confidence: 98%
“…Thirty-two years have passed since Parker [1983] published his literature review of throughfall and stemflow in the nutrient cycles of forests (see glossary for key terms, Appendix A) and 12 years since Levia and Frost [2003] published their review article on stemflow in the hydrologic and biogeochemical cycles of forested and agricultural ecosystems. Recognizing the complexity of water flux and the importance of stemflow in the hydrologic cycle of forests (Figure 1), another review specifically focusing on some stemflow studies in Japan was published by Ikawa [2007], while Johnson and Lehmann [2006] focused on the double funneling of stemflow above ground and below ground. In addition, Levia et al [2011a] reviewed some past throughfall and stemflow work and identified some future directions for stemflow research.…”
Section: Introductionmentioning
confidence: 99%